Prevalence and risk factors of dry eye disease in North India: Ocular surface disease index-based cross-sectional hospital study - Jeewan Singh Titiyal (Indian Journal of Ophthalmology, 2018)
Purpose: This study aims to study the prevalence of DED and analyze risk factors in North Indian population. Methods: This was a cross-section hospital-based, observational study. Cases enrolled over 2 years (systematic random sampling) were administered ocular surface disease index questionnaire to evaluate the prevalence and risk factors of DED. Schirmer's test and tear break-up time were performed only in the subset of patients giving consent. Categorical data were assessed with Chi-square/Fisher's Exact test, and odds ratio was analyzed using bivariate and multivariate logistic regression. P < 0.05 was statistically significant. Results: A total of 15,625 patients were screened. The prevalence of DED was 32% (5000/15625); 9.9% (496/5000) had mild DED; 61.2% (3060/5000) had moderate DED; and 28.9% (1444/5000) had severe DED. Age group of 21–40 years, male sex, urban region, and desk job were associated with increased risk of DED. Hours of visual display terminal (VDT) usage significantly correlated with DED (P < 0.001), and 89.98% of patients with 4 h or more of VDT use had severe dry eye. Cigarette smoking and contact lens usage had increased odds of developing severe DED (P < 0.001). Objective tests were undertaken in 552 patients; of these, 81.3% (449/552) had severe DED. Conclusions: The prevalence of DED in North India is 32%, with the age group of 21–40 years affected most commonly. VDT use, smoking, and contact lens use were associated with increased odds of developing DED.